RANCANG BANGUN SISTEM INFORMASI KEUANGAN DANA BOS BERBASIS WEB - Ni Kadek Ariasih; Anom Wiadnyana Putra (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTAt SMK PGRI 6 Denpasar previously using Microsoft Excel, but the number of transactions and reporting of BOS fund accountability was made three periods a year, so it is necessary to build a system that is effective, efficient and provides a good database. the author integrates the system by creating a financial reporting system in order to assist the admin in managing finances and reporting accountability for the use of BOS funds. The method used is the waterfall development method with blackbox testing testing techniques. The system has been built according to the design and the results of the blackbox testing of 31 scenarios obtained are in accordance with the design. The results achieved in building a financial information system for BOS funds at SMK PGRI 6 Denpasar were to assist the treasurer in the LPJ reporting process for the use of BOS funds, only by inputting transactions into the system automatically generates the required reports and can minimize the occurrence of data errors. This BOS fund financial information system produces outputs in the form of a general cash book, cash subsidiary ledger, bank subsidiary ledger, tax subsidiary ledger, details of the use of BOS funds, recapitulation of the realization of the use of BOS funds.Keywords: System, information, BOS funds financial report.ABSTRAKPada SMK PGRI 6 Denpasar sebelumnya sudah menggunakan Microsoft Excel namun banyaknya transaksi dan pelaporan pertanggungjawaban dana BOS dibuat tiga periode setahun, sehingga diperlukan dibangun sebuah sistem yang efektif, efisien dan memberikan database yang baik. penulis mengintegrasi sistem dengan membuat sistem laporan keuangan agar dapat membantu admin dalam mengelola keuangan dan laporan pertanggungjawaban penggunaan dana BOS.Adapun metode yang digunakan yaitu metode pengembangan waterfall dengan teknik pengujian blackbox testing. Sistem telah dibangun sesuai rancangan dan hasil dari pengujian blackbox testing dari 31 skenario yang didapat hasil telah sesuai dengan rancangan. Hasil yang dicapai dalam membangun sistem informasi keuangan dana BOS pada SMK PGRI 6 denpasar adalah membantu bendahara dalam proses pelaporan LPJ penggunaan dana BOS, hanya dengan menginput transaksi kedalam sistem secara otomatis menghasilkan laporan yang dibutuhkan serta dapat meminimalkan terjadinya kesalahan data. Sistem informasi keuangan dana BOS ini menghasilkan output berupa buku kas umum, buku pembantu kas, buku pembantu bank, buku pembantu pajak, rincian penggunaan dana BOS, rekapitulasi realisasi penggunaan dana BOS.Kata Kunci : Sistem, informasi, laporan keuangan dana BOS